PENGARUH JUMLAH KREDIT YANG DIBERIKAN, TINGKAT LIKUIDITAS, CAR TERHADAP PROFITABILITAS - Siti Nurmaidah, 08.05.52.0090; Anggono, Greg (Students Journal of Accounting and Banking, 2012)
The purpose of this research was to test and analyze the effect of the credit provided, level of Liquidity and capital adequacy level of profitability of the banking company registered at Bank Indonesia. Population taken in this research is banking companies listed on Bank Indonesia of 2007-2009. Samples taken by using centrifugal purpose sampling, namely samples selected on the basis of conformity characteristics by criteria determined. criteria obtained samples prepared 38 company.To test hypotheses asked in this research data analyzed by using test linear regression of multiple. Based on the results of the analysis can be inferred that variable (1) credit given the positive effect of the Return On Asset with a level of significance of 0.046. The greater the amount of credit given then the greater the ROA to be retrieved anyway.(2) there has been a positive influence on the Return On Asset Liquidity with a level of significance of 0.001. The higher the LDR at a low liquidity increasingly impacting companies and (3) Capital Adequecy Ratio effect positively to Return on Asset with a level of significance of 0.030. That the capital ratio is very important in the business of banking activities in operasinalnya in order to run smoothly.Keyword :Credit, Loan to Deposit Ratio, Capital Adequecy Ratio (CAR) and Return On Equity (ROA).